Impact of elevated atmospheric O3 on the actinobacterial community structure and function in the rhizosphere of European beech (Fagus sylvatica L.) - Schloter, Michael (Frontiers in Microbiology, 2014)
Many bacteria belonging to the phylum of Actinobacteria are known as antagonists against phytpathogenic microbes. This study aimed to analyze the effect of ozone on the actinobacterial community of the rhizosphere of four years old European beech (Fagus sylvatica L.) trees during different time points of the vegetation period. Effects of ozone on Actinobacteria were studied on the structural level of the community (16S rRNA gene), as well as on the functional level using primers targeting type II polyketide synthases (PKS) genes by fingerprinting and clone library analysis. Season as well as ozone treatments had a significant effect on parts of the actinobacterial rhizosphere community of European beech. However on the basis of the performed analysis, the diversity of Actinobacteria possessing type II PKS genes is neither affected by seasonal changes, nor by the ozone treatments, indicating no influence of the investigated treatments on the biocontrol active part of the actinobacterial community.